Analysis of Current and Electromagnetic Force Acting on Winding in cases of Short Circuits of Amorphous Transformer - Bao Doan Thanh; Chi Phi Do; Huynh Duc Hoan; Le Thai Hiep (My University, 2023)
Analysis of Current and Electromagnetic Force Acting on Winding in cases of Short Circuits of Amorphous Transformer
Keywords: Lực điện từ ngắn mạch; Dây quấn máy biến áp; Amorphous core